Geographical labor market imbalances : recent explanations and cures - Mussida, Chiara; Pastore, Francesco (AIEL Series in Labour Economics,, 2015)
This book focuses on the questions of how territorial differences in productivity levels and unemployment rates arise in the first place and why territorial differences in labor market performance persist over time. Unemployment divergence and unemployment club convergence have been touched on in a large number of works and have recently also been studied using spatial econometric analysis. In this book we aim to develop the debate to include several important new topics, such as: the reasons why structural changes in some sectors cause slumps in some regions but not in others; the extent to which agglomeration factors explain regional imbalances; the degree of convergence / divergence across EU countries and regions; the role of labor mobility in reducing / increasing regional labor market imbalances; the impact of EU and country-level regional policy in stimulating convergence; and the (unsatisfactory) role of active labor market policy in stimulating labor supply in the weakest economic areas.